Gendered intergenerational transmission of work values?: a country comparison - Cemalcilar, Zeynep; Jensen, Carsten; Tosun, Jale (The annals of the American Academy of Political and Social Science, 2019)
In this study, we examine two research questions: Are the work values of young people determined by the work values of their parents? Is the transmission of work values conditioned by the young adults’ gender? We use original survey data for respondents aged 18-35 and their parents in Denmark, Germany, Turkey, and the UK to explore these questions. Our findings reveal a robust pattern: in all four countries and for all four types of work values we measure, young adults’ work values are strongly influenced by their parents’ work values. We also find a gender effect among German respondents: work plays a more central role in the lives of young men than in the lives of young women. Gender helps to explain attitudes toward female labor force participation in all of the countries we studied, and we find no evidence that gender conditions the effect of the intergenerational transmission of work values except for in the UK, where gender does condition the effect of family attitudes on young peoples’ extrinsic work values and their views on work centrality.
Gesehen am 08.05.2019